Correlation of physical and mechanical properties with ultrasonic pulse velocities of sandstones in Çenedağ, Kocaeli-Turkey - Aşcı, Metin; Kaplanvural, İsmail; Karakaş, Ahmet; Şahin, Özgün Kamil; Kurtuluş, Cengiz (International Journal of Advanced Geosciences, 2017)
Correlation of physical and mechanical properties with ultrasonic pulse velocities (UPV) of sandstones in Çenedağ, Kocaeli-Turkey, NW was performed in this study. Physical and mechanical properties were defined and the relationships among the uniaxial compressive strength (UCS), porosity, void ratio, point load strength index Is(50),Schmidt hardness (RN) and bulk mass density by weight with ultrasonic pulse velocity of pink and cream colored sandstone unit of Lower Ordovician Çenedağ formation were investigated. In the scope of this research, 16 sandstone specimens were collected from various locations of Çenedağ formation in Çenedağ-Kocaeli, Turkey and laboratory experiments were implemented. Later, the statistical correlations were performed by regression analysis to evaluate the relationships between these properties and ultrasonic pulse velocity. Reasonably good correlations were determined between the UPV and physical and mechanical properties.